Test Of Stability Of Physical And Activity AntibacterialEssential Oil Nutmeg ( Myristica Fragrans Houtt . ) To Bacteria Staphylococcus Aureus Against In Liquid Soap Formulations - Farah Irmalia, Sari; , Suprapto, M.Sc.,Apt; , Rima Munawaroh, M.Sc., Apt (2016)
Nutmeg essential oil contains compounds myristicin 1.1%, elimicin 1%, and 0.1% safrole. Active substance that is antibacterial that is myristicin that in this study were formulated in liquid soap. This study aims to determine the effect of KOH concentration and stearic acid on the physical properties and stability of liquid soap and essential oils of nutmeg activity against Staphylococcus aureus. Liquid soap were made with the concentration ratio of KOH: stearic acid in Formula I (1,6g: 1g), Formula II (3,2g: 0,5g), Formula III (6,4g: 0,25g), and Formula IV (12, 8g: 0,125g). The concentration of essential oils of nutmeg used 25% v/v. Preparations tested physical properties include organoleptic, pH, viscosity, foam, weight and the type of free alkali content is analyzed using one- way ANOVA and Kruskal-Wallis. Organoleptic test include stability, pH, viscosity and height were analyzed using General Linear Model Univariant. One final test of antibacterial test pitting diffusion method. Physical properties test results showed increased KOH concentration increases the pH value, the specific gravity and the free alkali content, while increasing the stearic acid increases the viscosity and foam. Results of stability tests show variation formula lowers the stability of preparations, so that the preparation does not stable in storage for two months. Antibacterial test results showed that the liquid soap is irradikal against Staphylococcus aureus.